Indonesian Fish Policy Development and Marketing Strategy In The Context of Utilizing Market Potential - Ngamal, Yohanes; Setiawati , Eka (Publikasi Indonesia, 2023)
The sea is an important part and is a natural resource that drives economic growth. Apart from that, the sea is also an asset for Indonesia. Currently the Indonesian government is fully concentrating on maritime development and wishes to become the world's maritime axis. However, it should be realized that maritime development issues are not as easy as one might think. Various complicated problems that arise from the internal and external environment which are obstacles and must be resolved first. To solve this problem the government needs to build a maritime management system, so that the sea is no longer just a name or symbol for Indonesia as a maritime country but also as one of the economic sectors that presents products or services where the results can encourage people's welfare.